Temporal measures in cardiac structure and function during the development of obesity induced by different types of western diet in a rat model - Vileigas, Danielle Fernandes [UNESP]; Marciano, Cecília Lume de Carvalho [UNESP]; Mota, Gustavo Augusto Ferreira [UNESP]; de Souza, Sérgio Luiz Borges [UNESP]; Sant’ana, Paula Grippa [UNESP]; Okoshi, Katashi [UNESP]; Padovani, Carlos Roberto [UNESP]; Cicogna, Antonio Carlos [UNESP] (MDPI, 2020)
Obesity is recognized worldwide as a complex metabolic disorder that has reached epidemic proportions and is often associated with a high incidence of cardiovascular diseases. To study this pathology and evaluate cardiac function, several models of diet-induced obesity (DIO) have been developed. The Western diet (WD) is one of the most widely used models; however, variations in diet composition and time period of the experimental protocol make comparisons challenging. Thus, this study aimed to evaluate the effects of two different types of Western diet on cardiac remodeling in obese rats with sequential analyses during a long-term follow-up. Male Wistar rats were distributed into three groups fed with control diet (CD), Western diet fat (WDF), and Western diet sugar (WDS) for 41 weeks. The animal nutritional profile and cardiac histology were assessed at the 41st week. Cardiac structure and function were evaluated by echocardiogram at four different moments: 17, 25, 33, and 41 weeks. A noninvasive method was performed to assess systolic blood pressure at the 33rd and 41st week. The animals fed with WD (WDF and WDS) developed pronounced obesity with an average increase of 86.5% in adiposity index at the end of the experiment. WDF and WDS groups also presented hypertension. The echocardiographic data showed no structural differences among the three groups, but WDF animals presented decreased endocardial fractional shortening and ejection fraction at the 33rd and 41st week, suggesting altered systolic function. Moreover, WDF and WFS animals did not present hypertrophy and interstitial collagen accumulation in the left ventricle. In conclusion, both WD were effective in triggering severe obesity in rats; however, only the WDF induced mild cardiac dysfunction after long-term diet exposure. Further studies are needed to search for an appropriate DIO model with relevant cardiac remodeling.
Keywords: Cardiac dysfunction; Cardiac remodeling; Echocardiogram; High-fat high-sugar diet; Obese rats